Educational, Economic, Social, and Environmental Empowerment with PT. Rimba Makmur Utama (RMU) in Terantang Hilir Village - Napiah, Muhammad Ali; Hasanah, Rabiatul; Ulfah, Zaida; Maulana, Amin; Setianingrum, Fianggi; Nadila, Nanda; Sofia, Sofia; Amin, Muhammad (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2025)
The Preamble to the Mandate of the 1945 Constitution encouraged KKN Group 68 IAIN Palangkaraya students to empower education, the economy, social, and environmental in collaboration with a third party PT. Rimba Makmur Utama (RMU) in Terantang Hilir village. This research uses field research with primary data collection techniques from the community and children in Terantang Hilir village. Secondary data in this research was collected in the form of documents, books, and articles related to service journals. The results of this research are the role of students in community service, or what is usually called real work lectures (KKN). This improves the quality of education, the economy, social aspects, and the village environment. In the field of education, group 68 KKN students were the initiators in conceptualizing the problem of reading and distributing forest and land fire comic books. Economically, group 68 KKN students helped the Humbang Hanyar farmer group in marketing essential oil products in the form of making logos, promotions (IG accounts and brochures), and Navigation of the production house. In social and environmental aspects, KKN group 68 students play an active role in community/agency activities in the village to strengthen social relations between residents, as well as contributing to environmental clean-up programs that help preserve the village’s nature.